American Orientalism in Korean Vietnam War Novels: A Case Study of The Shadow of Arms and The Faraway Ssongba River - Surakitbovorn, Siwat (Journal of Social Sciences Naresuan University, 2025)
This research article aims to explore and understand the origins of American Orientalism, which began to take shape from the Korean War to the Vietnam War. Although in the 1960s, Orientalism was a concept rooted in European colonialism, South Korean scholars acknowledged that South Korean society in the Post-Korean War era was significantly influenced and shaped by American imperialist ideology. This led to the transmission and reproduction of Western ideals within South Korean society, embedding Orientalist perspectives into various art forms, including print media, textbooks, television shows, and films. The novel The Faraway Ssongba River by Park Young-han interprets American Orientalism as the United States use of financial power through the U.S. dollar to fully intervene in and control the economic systems of Vietnam. Meanwhile, The Shadow of Arms by Hwang Seok-young presents representations of racism and sexism, and portrays Asian individuals perceived as inferior in comparison with South Koreans. Analyzing American Orientalism through these two literary works reveals how this ideology was instilled and reproduced through the worldviews of authors who returned from the battlefield of the Vietnam War. Although both authors used their literary works to critique American imperialist power and viewed the United States as intervening in Asian countries through both hard and soft power, they could not transcend the dominant aspiration prevalent in South Korean society at that time—specifically, the strong desire for transformation toward American-style modernity.